Consequences of Interpersonal Capitalization in the Workplace - Syofyan Hadi; M. Rasyid Abdillah; Adi Rahmat (Yayasan Education Al Aqsho Modern, 2022)
The purpose of this study is to explain the impact of interpersonal capitalization in the workplace on emotional reactions and employee behavior such as inspiration and jealousy, as well as its impact on interpersonal citizenship behavior (ICB) and social undermining. This study will use and utilize a cross-sectional research design to examine the relationship that has been hypothesized in the previous chapter. Individual perception data will be collected using a questionnaire consisting of a predetermined scale and size. In the next section, the sample, data collection procedures, and steps used in this study will be discussed. Respondents in this study were 340 police officers who work in several police institutions located in one area in Indonesia. The number of research samples of 340 respondents was determined based on 10 to 20 times the number of question/statement items (29 statement or question items). The findings of this study can also provide input to the organization's management in considering interpersonal capitalization strategies in certain contexts.